2019
DOI: 10.9734/jamps/2018/v19i430096
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Anti-inflammatory Activities of Triterpenoid Molecules Isolated from the Leaves of Combretum glutinosum Perr. Ex DC (Combretaceae)

Abstract: Combretum glutinosum Perr. Ex DC (COMBRETACEAE) is a traditional medicinal plant, widely distributed in Senegal and Africa. The aim of that study was to investigate the analgesic and anti-inflammatory activities of two triterpenes, betulonic acid (DN7) and cabraleone (DN12), isolated from the leaves of Combretum glutinosum. Experiments were performed in acetic acid-induced contortions in mice and carrageenan rat paw oedema. DN7 (3 mg/kg, per os) and DN12 (3 mg/kg, per os) significantly prevent contortions in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Au Sénégal, Sène et al ( 2018) ont étudié les activités analgésique et antiinflammatoire de deux triterpènes (acide bétulonique et cabraléone) isolés des feuilles de C. glutinosum sur des contorsions induites par l'acide acétique chez la souris et sur l'oedème de la patte de rat induit par la carragénine. Leurs activités analgésique et anti-inflammatoire étaient similaires à celles des médicaments anti-inflammatoires non stéroïdiens tels que l'acide acétylsalicylique, ce qui justifie son utilisation en médecine traditionnelle pour traiter la douleur et l'inflammation (Sene et al, 2018).…”
Section: Propriétés Analgésique Et Antiinflammatoireunclassified
“…Au Sénégal, Sène et al ( 2018) ont étudié les activités analgésique et antiinflammatoire de deux triterpènes (acide bétulonique et cabraléone) isolés des feuilles de C. glutinosum sur des contorsions induites par l'acide acétique chez la souris et sur l'oedème de la patte de rat induit par la carragénine. Leurs activités analgésique et anti-inflammatoire étaient similaires à celles des médicaments anti-inflammatoires non stéroïdiens tels que l'acide acétylsalicylique, ce qui justifie son utilisation en médecine traditionnelle pour traiter la douleur et l'inflammation (Sene et al, 2018).…”
Section: Propriétés Analgésique Et Antiinflammatoireunclassified
“…Also, many pharmacological studies have reported the therapeutic potential of C. glutinosum extracts. These studies mostly focus on antioxidant [11], antiparasitics [12][13][14], antidiarrheal [15], antihyperglycemic and cytotoxic [16], antibacterial [17] and anti-inflammatory [18] activities. This study participates to the valorization of traditional medicinal plants and aims to highlight the anti-inflammatory and healing activities of the methanolic fraction of the bark of C. glutinosum.…”
Section: Research Articlementioning
confidence: 99%
“…Four triterpenoids (betulinol, betulonal, betulonic acid and cabraleone) were isolated from the hexane and dichloromethane extracts of the leaves (Diaye et al, 2017). Two of these compounds (betulonic acid and cabraleone) demonstrated significant analgesic and antiinflammatory activity (Sene et al, 2019). Moreover, betulin and its semisynthetic derivatives such as 28-O-(N-acetylanthraniloyl) betulin have been found to possess considerable antibacterial activity against , S. aureus and E. faecalis (MIC90 of 6.25 µM) (Haque et al, 2014).…”
Section: 21antibacterial Activitymentioning
confidence: 99%